2021
DOI: 10.1021/acs.joc.1c02576
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Hydroamination of Oxa- and Azabenzonorbornadienes with Pyrazoles

Abstract: An efficient and highly chemo- and stereoselective copper-catalyzed hydroamination of oxa- and azabenzo­norbornadienes with various pyrazole derivatives is described. This catalytic process is promoted by the presence of N-heterocyclic carbene ligands and KOt-Bu under mild and simple reaction conditions, and allows for the direct synthesis of new and versatile functionalized oxa­(aza)­benzo­norbornyl pyrazoles starting from readily available oxa­(aza)­bicyclic alkenes. The synthetic utility of this method was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…The selected pyrazoles 10-4 bearing a variety of substituents were successfully applied to this protocol and provided the corresponding exo-selective addition products 10-5 in good to excellent yields (up to 98%). [31]…”
Section: Hydroaminationmentioning
confidence: 99%
See 2 more Smart Citations
“…The selected pyrazoles 10-4 bearing a variety of substituents were successfully applied to this protocol and provided the corresponding exo-selective addition products 10-5 in good to excellent yields (up to 98%). [31]…”
Section: Hydroaminationmentioning
confidence: 99%
“…However, the palladacycle could effectively accelerate the reaction and furnish the desired functionalized methylenecyclopropanes 35-1 in moderate to good yields (42~88%). Moreover, by 31 P NMR spectrum studies, they revealed that the palladacycle was the real transition metal catalyst and the structure of the palladacycle was kept intact in the reaction. [66] Yamaguchi and co-workers reported the [2 + 1] cycloaddition reaction of sulfur to bicyclic alkenes by employing the rhodium complex derived from RhH(PPh 3 ) 4 , dppe, and 4-ethynyltoluene (Scheme 36).…”
Section: [2 + 1] Cyclizationmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Our group has recently reported the efficiency of potassium tert -butoxide (KO t -Bu) in promoting the reactivity of the intermolecular hydroamination of indoles with allylic sulfones and controlling the chemo- and regioselectivity of indole addition under mild reaction conditions. 9,10 Gunanathan et al also reported that the aza-Michael addition of azoles to α , β -unsaturated nitriles was efficiently catalyzed by KO t -Bu, even though the substrate scope was limited to acyclic terminal alkenes. 7 e KO t -Bu as a catalyst has the advantage of being inexpensive, abundant and readily accessible.…”
Section: Introductionmentioning
confidence: 99%
“…As a parallel class of strained olefins, 7-oxa- and 7-azabenzonorbornadienes have been widely employed in both ring-retentive and ring-opening catalytic transformations, including hydrofunctionalization and C–H activation reactions (Scheme b and c, respectively). In particular, chelation-assisted C–H functionalization followed by annulation with a bifunctional directing group provided an efficient route to access polycyclic heterocycles .…”
mentioning
confidence: 99%